ChemInform Abstract: Cu‐Catalyzed Cross‐Dehydrogenative Coupling Reactions of (Benzo)thiazoles with Cyclic Ethers. Issue 4 (28th January 2014) - Xie, Zengyang; Cai, Yuping; Hu, Hongwen; Lin, Chen; Jiang, Juli; Chen, Zhaoxu; Wang, Leyong; Pan, Yi
Abstract The novel mild method allows the formation of new C‐C bonds between thiazoles and cyclic ethers.